Characterisation of electron beam melting process on Ti6Al4V in order to guide finishing operation. (2015) - Dolimont, Adrien; Michotte, Sébastien; Rivière-Lorphèvre, Edouard; Ducobu, François; Formanoir, Charlotte De; Godet, Stéphane; Filippi, Enrico
There is still a lack of standards in the fast growing Additive Manufacturing (AM) field and efforts are still required to improve parts reliability, consistency and quality. The aim is to define machining allowance for the Electron Beam Melting (EBM) process on Ti6Al4V, which still needs finishing step. Analysis on the dimensions obtained was carried out over a large number (110) of raw printed parts having the same geometry using a coordinate measuring machine (CMM). The geometric and dimensional tolerances were highlighted. A micro-geometrical analysis was also carried out to determine the roughness dispersion. A capability analysis was conducted to define the class of tolerance for EBM process. The results show that the Interval of Tolerances (IT) class is close to sand casting process for dimensional characterisation (IT15 or even IT12 if systematic errors are suppressed). This study is carried out in order to guide finishing operations occurring after AM.